Artists and the Public's Attention Since the 1960s: An Exploration of How Artists Seek to Capture the Audience's Attention - van Rossem, Patrick (The Nordic Journal of Aesthetics, 2023)
Art historical research shows that artists, especially since the 1960s rise in museum and art gallery attendance do not always trust the audience’s ability to deal with their art. The choice for a performative aesthetic, for example, has also been a method for reasserting rather than—as is often thought—relinquishing artistic control. The article looks at aesthetic strategies developed by artists who desire(d) a more attentive look from their audiences. It considers works made by artists in the sixties and seventies. It is a fact that the appearance of mass audiences goes hand in hand with the creation of artworks that have “attention” as their subject. Secondly, the article takes a look at more contemporary work. Faced with spectators that spend about 28 seconds looking at artworks and reading the accompanying labels, artists are developing strategies that slow spectators down, thus hoping to channel and hold their attention.